Understanding yeast glycolysis dynamics using HPLC analysis and mathematical modelling. - Van Schalkwyk, Clara Elizabeth (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.